A Well-Researched Book in Search of an Audience: Making Sense of Genes by Kostas Kampourakis - Findlay, Geoffrey D. (CBE Life Sci Educ, 2018)
Making Sense of Genes is a new book by Kostas Kampourakis that offers a well-researched commentary on the strengths and limitations of genetics. The book may be too scientifically complex and too one-sided in its opinions to assign to undergraduate students, but it is a provocative and useful read for instructors planning a genetics course.